Peningkatan Pengetahuan Kelompok Nelayan Tentang Bantuan Hidup Dasar Melalui Media Audiovisual - Adiratna Sekar Siwi; Made Suandika; Indri Wijayanti; Arif Imam Hidayat (LPPM Universitas Harapan Bangsa Purwokerto, 2023)
Drowning is one of the emergency cases in the water and is dangerous and life threatening. The number of deaths due to drowning is due to the inappropriate and inappropriate rescue system and knowledge of handling Basic Life Support (BHD) for drowning victims. The provision of BHD has a big role in determining the success of the help provided. This counseling activity was carried out with lectures, viewing videos on Basic Life Support and question and answer discussions. This activity was carried out on July 26, 2022, attended by fishermen groups around Jetis beach, Cilacap, totaling 30 participants. The results of measuring fishermen's knowledge about BHD have increased the score from before counseling 13.63 to 16.47. counseling using audiovisual media can improve respondents' memory. After the implementation of this activity, it is hoped that the fishermen group will have the skills and have certification in assisting the handling of drowning victims.